Competency assessment: Critical Educational Model with Focus on Competencies (volume 3) (2021)
The main objective of this book is to analyze evaluation as a fundamental process to ensure quality training based on competencies. The three works that make up this third volume account for all of the above. The chapter "Competency Assessment Strategy: Contextualized Practices and the Critical Educational Model through a Participatory Methodology" aims to analyze, from the perspective of competencies at the University, the forms of assessment that teachers use with their students and how In turn, they identify and understand these practices to finally propose improvement strategies that apply to the educational model adopted by the University. The second investigation, entitled "The evaluation of competences: the systematization of an innovative experience at the Cooperative University of Colombia", aims to systematize how the design and application of tests for the evaluation of generic and transversal competencies are made, to optimize the evaluation processes within the institution. To conclude, the investigation called "The evaluation by competences of teaching performance as a strategy of continuous improvement", seek to identify which are the differentiated criteria within the Educational Model for the evaluation of the teacher, so that a rubric can be proposed that allows the development of this process in all its dimensions.